2012
DOI: 10.1051/0004-6361/201118146
|View full text |Cite
|
Sign up to set email alerts
|

Water in star-forming regions withHerschel(WISH)

Abstract: Context. Water is a key tracer of dynamics and chemistry in low-mass star-forming regions, but spectrally resolved observations have so far been limited in sensitivity and angular resolution, and only data from the brightest low-mass protostars have been published. Aims. The first systematic survey of spectrally resolved water emission in 29 low-mass (L < 40 L ) protostellar objects is presented. The sources cover a range of luminosities and evolutionary states. The aim is to characterise the line profiles to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
589
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 260 publications
(669 citation statements)
references
References 114 publications
71
589
8
Order By: Relevance
“…supersonic infall. The infall velocity and derived infall rates are consistent with the values derived by Kristensen et al (2012) for a small sample of low-mass protostars. It is important to note that for source A we could not identify an inverse P-Cygni profile, if present, because of the steep velocity gradient.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…supersonic infall. The infall velocity and derived infall rates are consistent with the values derived by Kristensen et al (2012) for a small sample of low-mass protostars. It is important to note that for source A we could not identify an inverse P-Cygni profile, if present, because of the steep velocity gradient.…”
Section: Resultssupporting
confidence: 86%
“…Since the front absorbing layer is probably subthermally excited, we assumed a conservative value for the excitation front layer of T f = 3 K. The continuum temperature, T c , was chosen such that the continuum radiation temperature, J c (T c ), matches the peak continuum flux in the image. The continuum source beam filling fraction, Φ, which is not well constrained, was set to 0.3 to use the same value as Di Francesco et al (2001), who modeled interferometric observations with a similar angular resolution as we did; this value is consistent with the line modeling results of coarse angular resolution Herschel data Kristensen et al (2012). Although the value of Φ used here is arbitrary, we have also performed line profile fits with higher values of Φ and the obtained infall velocity and velocity dispersion are unchanged, while the values for T r and τ 0 are increased and decreased, respectively.Similarly, if a higher value of T c is used, T r and τ 0 are increased and decreased, respectively, while we obtain the same results for V in and σ v .…”
Section: Appendix A: the Two-layer Modelmentioning
confidence: 59%
See 2 more Smart Citations
“…More recently, water emission observed with HIFI (Santangelo et al 2012) was suggested to originate in J-shocks, which is not consistent with the findings from the shock model comparisons above. However, Kristensen et al (2012) has shown that the water line profiles resolved with HIFI are complex, tracing simultaneously more than one processes.…”
Section: Discussionmentioning
confidence: 99%